Composite polyester fiber as well as preparation method and application thereof
By controlling the characteristics of core and cortical materials and using high-precision spinnerets, composite polyester fibers with good uniformity were prepared, which solved the problem of poor uniformity of composite fibers in the prior art, and significantly improved in cell culture. Sugar metabolism capacity.
Patent Information
- Application Number
- CN202311048379.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
It is difficult to effectively obtain highly uniform ultrafine composite fibers in the prior art, especially as the fibers become thinner and thinner, controlling fiber uniformity becomes more difficult.
Composite polyester fibers with a leather core structure were prepared by controlling the dosage ratio, melting point difference, intrinsic viscosity difference and standard deviation of the core layer and the use of high-precision spinnerets. The specific steps include melting the core layer material and the leather layer material separately to form a melt, and then spinning it through a spinneret to form a composite fiber with good uniformity.
The composite polyester fiber has a small diameter and a small standard deviation of diameter, which significantly improves the uniformity of the fiber. Preferably, the use of such fibers can significantly improve the sugar metabolism capacity of the cells, thereby improving the reproduction and survival rate of the cells.
Smart Images

Figure BDA0004406517290000071 
Figure BDA0004406517290000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite polyester fibers, and in particular to a composite polyester fiber and a preparation method and application thereof. Background Art
[0002] Polyester fiber is a product that uses polyester in the form of fiber. The most commonly used polyester material is polyethylene terephthalate (PET), and other polyesters such as polybutylene terephthalate and polylactic acid are also used. The methods for preparing polyester into fibers can be roughly divided into melt spinning and solution spinning. Solution spinning is divided into dry spinning and wet spinning depending on whether the solvent used is a volatile solvent. Melt spinning can be simply divided into direct spinning, mixed spinning and composite spinning. Among them, the composite spinning method can obtain composite fibers.
[0003] Composite fiber refers to chemical fiber made of two or more polymers, or the same polymer with different properties, through composite spinning. According to the different distribution of the two types of polymers on the cross section, it can be divided into skin-core type, orange segment type, island-in-the-sea type and parallel type.
[0004] Improving the uniformity of fibers has always been the direction pursued by the industry. In the past, the uniformity of polyester fibers, which were mainly used for clothing weaving, did not need to be too high, but with the improvement of the quality of life, some new products have begun to have higher requirements for the uniformity of fibers. It is well known in the industry that as fibers become thinner and thinner, the uniformity of fibers becomes more and more difficult to control. Moreover, due to the unevenness of the materials, the difficulty of controlling the uniformity of composite fibers is significantly greater than that of direct-spun fibers. In terms of direct-spun fibers, CN107893264B obtains relatively uniform direct-spun polyester ultrafine filaments (<3dtex, i.e., a diameter of less than 20μm) by adopting a larger slow cooling chamber and a crown ether oiling agent; WO2022134653 prepares relatively uniform direct-spun PET ultrafine fibers (5D-7D, i.e., a diameter of 24-29μm) by using a DIO spinning assembly and relatively uniform heating. However, in the prior art, there is a lack of effective methods for obtaining highly uniform ultrafine composite fibers. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of poor uniformity of thickness of polyester fibers in the prior art, and to provide a polyester fiber and a preparation method and application thereof.
[0006] The inventors found in the research process that by controlling the amount ratio of the core layer and the skin layer material, the difference in melting point, the difference in intrinsic viscosity and the standard deviation of the core layer and the skin layer material, and using a high-precision spinneret, a composite polyester fiber with good thickness uniformity can be obtained. Therefore, the first aspect of the present invention provides a method for preparing a polyester fiber, the method comprising: melting the core layer material and the skin layer material separately to obtain a melt, and then spinning the melt to obtain a composite polyester fiber with a skin-core structure;
[0007] The melting point of the core material is higher than that of the skin material by more than 22°C; the intrinsic viscosity of the skin material is 0.01-0.15 dL / g higher than that of the core material, and the standard deviation of the intrinsic viscosities of the core material and the skin material is ≤0.02 dL / g; the mass ratio of the core material to the skin material is x, 1.5≤x≤4;
[0008] The spinneret holes of the spinneret plate used in the spinning process are in the shape of concentric circles, the difference between the maximum diameter and the minimum diameter of each circle of the spinneret holes is ≤2 μm, and the difference between the maximum diameter and the minimum diameter of each outer circle is ≤2 μm.
[0009] The second aspect of the present invention provides a composite polyester fiber prepared by the method described above.
[0010] A third aspect of the present invention provides a polyester fiber cloth, which is prepared by using the composite polyester fiber described above.
[0011] The fourth aspect of the present invention provides use of the composite polyester fiber or the polyester fiber cloth described above in cell culture.
[0012] Through the above technical solution, the present invention achieves the following beneficial effects:
[0013] (1) The composite polyester fiber of the present invention has a small diameter and a small standard deviation of the diameter, which indicates that the ultrafine polyester fiber of the present invention has good uniformity.
[0014] (2) Preferably, the composite polyester fiber of the present invention can significantly improve the sugar metabolism ability of cells. The higher the sugar metabolism ability, the higher the cell reproduction rate and survival rate (only living cells can metabolize sugar, and dead cells cannot metabolize sugar). That is, the composite polyester fiber can achieve better results when used for cell culture. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] The first aspect of the present invention provides a method for preparing polyester fiber, the method comprising: melting a core layer material and a skin layer material separately to obtain a melt, and then spinning the melt to obtain a composite polyester fiber with a skin-core structure;
[0017] The melting point of the core material is higher than that of the skin material by more than 22°C; the intrinsic viscosity of the skin material is 0.01-0.15 dL / g higher than that of the core material, and the standard deviation of the intrinsic viscosities of the core material and the skin material is ≤0.02 dL / g; the mass ratio of the core material to the skin material is x, 1.5≤x≤4;
[0018] The spinneret holes of the spinneret plate used in the spinning process are in the shape of concentric circles, the difference between the maximum diameter and the minimum diameter of each inner circle of the spinneret holes is ≤2 μm, and the difference between the maximum diameter and the minimum diameter of each outer circle is ≤2 μm.
[0019] In the present invention, the difference between the maximum diameter and the minimum diameter of each inner circle or each outer circle can be independently 0.1 μm, 0.5 μm, 1.5 μm, 2 μm, and a range consisting of any two of the above points, such as 0.1-2 μm.
[0020] In the present invention, the test method for the intrinsic viscosity of polyester is the intrinsic viscosity test method described in GBT14190-2017. The test method for the standard deviation of the intrinsic viscosity is: randomly take 6 samples, test the intrinsic viscosity according to the intrinsic viscosity test method described in GBT14190-2017, and take the standard deviation of the values. The smaller the standard deviation of the intrinsic viscosity, the higher the uniformity of the intrinsic viscosity of the same batch of materials.
[0021] According to the present invention, the standard deviation of the intrinsic viscosity of the core layer material and the skin layer material can be independently 0.02dL / g, 0.018dL / g, 0.015dL / g, 0.01dL / g, 0.009dL / g, 0.008dL / g, 0.007dL / g, 0.006dL / g, 0.005dL / g, 0.004dL / g, 0.003dL / g, 0.002dL / g, 0.001dL / g, 0.0001dL / g, and the range formed by any two of the above points, for example 0.0001-0.02dL / g.
[0022] According to the present invention, the melting point of the core layer material is more than 22°C higher than the melting point of the skin layer material (for example, 22°C, 24°C, 25°C, 30°C, 40°C, 50°C, 60°C, 80°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, and a range formed by any two of the above points, for example 20-160°C). Preferably, the melting point of the core layer material differs from that of the skin layer material by more than 24°C.
[0023] According to the present invention, preferably, the core layer material is homopolyethylene terephthalate. More preferably, the intrinsic viscosity of the homopolyethylene terephthalate is 0.6-0.8 dL / g (e.g., 0.6 dL / g, 0.62 dL / g, 0.64 dL / g, 0.66 dL / g, 0.68 dL / g, 0.70 dL / g, 0.72 dL / g, 0.74 dL / g, 0.76 dL / g, 0.78 dL / g, 0.8 dL / g, and any of the above The melting point is above 240°C (for example, 240°C, 245°C, 248°C, 250°C, 255°C, 260°C, 265°C, 270°C, 280°C, 290°C, 300°C, 320°C, 350°C, 380°C, and a range consisting of any two points above), further preferably 245-280°C.
[0024] According to the present invention, preferably, the standard deviation of the intrinsic viscosity of the homopolyethylene terephthalate is ≤0.01 dL / g, more preferably ≤0.005 dL / g.
[0025] According to the present invention, preferably, the skin material is copolyethylene terephthalate; more preferably, the intrinsic viscosity of the copolyethylene terephthalate is 0.5-0.9 dL / g (e.g., 0.5 dL / g, 0.52 dL / g, 0.54 dL / g, 0.60 dL / g, 0.62 dL / g, 0.64 dL / g, 0.66 dL / g, 0.68 dL / g, 0.70 dL / g, 0.72 dL / g, 0.74 dL / g, 0.76 dL / g, 0.78 dL / g, 0.80 dL / g, The melting point is below 240°C (for example, 240°C, 230°C, 235°C, 220°C, 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 145°C, 140°C, 135°C, 130°C, 120°C, and the range formed by any two of the above points), more preferably 130-240°C.
[0026] According to the present invention, preferably, the standard deviation of the intrinsic viscosity of the co-polyethylene terephthalate is ≤0.015 dL / g, preferably ≤0.01 dL / g.
[0027] According to the present invention, preferably, the copolyethylene terephthalate comprises structural units from terephthalic acid, ethylene glycol and comonomer Y, and the content of the structural units from comonomer Y in the copolyethylene terephthalate is 0.6-18 mol% (for example, 0.6 mol%, 0.75 mol%, 1 mol%, 1.5 mol%, 3 mol%, 5 mol%, 10 mol%, 15 mol%, 18 mol%, and the range composed of any two of the above points), more preferably 0.7-15 mol%. In the present invention, the content of the structural unit of comonomer Y refers to: the percentage of the amount of the structural unit of comonomer Y to the total amount of the structural units of terephthalic acid, ethylene glycol and comonomer Y.
[0028] According to the present invention, the type of the comonomer is not particularly limited, as long as the melting point and intrinsic viscosity difference between the skin material and the core material and the standard deviation of the intrinsic viscosity can meet the requirements. Preferably, the comonomer Y is selected from at least one of dicarboxylic acids, diols and tetraols. More preferably, the dicarboxylic acid is a dicarboxylic acid containing a benzene ring, and is more preferably isophthalic acid and / or phthalic acid. More preferably, the diol is a diol having a carbon number of 3-20, and is more preferably at least one of butanediol, hexanediol, cyclohexanedimethanol and pentanediol (e.g., neopentanediol). More preferably, the tetraol has a carbon number of 3-20. In the present invention, the carbon number of the diol or tetraol can be 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 20 independently of each other.
[0029] In the present invention, the comonomer Y may also be selected from acid monomers in other forms such as anhydrides, acid chlorides, methanol esters, and ethanol esters, and the alcohol monomers include alcohol monomers in other forms such as ethers, hemiacetals, and acetals.
[0030] According to the present invention, preferably, the Sb content in the core layer material and the skin layer material of the polyester fiber is less than 20 ppm. In the present invention, "ppm" refers to the "weight" content.
[0031] In the present invention, the amount of the core layer material is higher than that of the skin layer material, and the mass ratio (weight ratio) of the core layer material to the skin layer material can be 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.2, 3.5, 3.8, 4, and the range of any two of the above points, preferably 2-3.6. Limiting the weight ratio of the core layer material to the skin layer material within the above preferred range can further improve the uniformity of the thickness of the composite polyester fiber, that is, obtain a smaller standard deviation of the diameter of the composite polyester fiber.
[0032] In the present invention, it can be understood that the core layer material passes through the inner circle of the spinneret hole to form the core layer structure of the composite polyester fiber, and the skin layer material passes through the outer circle of the spinneret hole to form the skin layer structure of the composite polyester fiber, and then is cooled and stretched to form a composite polyester fiber with a skin-core structure.
[0033] According to the present invention, preferably, the inner diameter of the inner circle of the spinneret is 15-25 μm, and the inner diameter of the outer circle is 25-35 μm. In the present invention, the precise aperture of the spinneret is measured by a profilometer.
[0034] According to the present invention, preferably, the process of spinning the melt to obtain a composite polyester fiber with a sheath-core structure comprises the following steps:
[0035] (1) feeding the melt into a spinneret for spinning to obtain a filamentary melt having a skin-core structure;
[0036] (2) using side blowing to cool the filament melt having a skin-core structure to obtain a nascent fiber;
[0037] (3) The spun fibers are stretched using high-speed airflow to obtain composite polyester fibers.
[0038] According to the present invention, preferably, the wind speed of the side wind is 1.5-2m / s (for example, 1.5m / s, 1.6m / s, 1.7m / s, 1.8m / s, 1.9m / s, 2m / s, and the range formed by any two of the above points), more preferably 1.5-1.8m / s; the temperature is 15-30℃ (for example, 15℃, 20℃, 25℃, 30℃, and the range formed by any two of the above points), more preferably 15-20℃.
[0039] According to the present invention, preferably, the flow rate of the high-speed airflow is 3000-5000 m / min. Preferably, the high-speed airflow stretching can further preferentially orient the fiber structure along the processing direction of the fiber, thereby making the fiber thickness more uniform on the one hand and making the mechanical properties of the fiber better on the other hand.
[0040] According to the present invention, preferably, the stretching method comprises at least one of a round tube stretching method, a slit stretching method and a swing wire method.
[0041] According to the present invention, preferably, the inner diameter of the round tube used in the round tube method is 0.5-5 cm, and the distance between two adjacent round tubes is 0.5-10 cm. The distance between two adjacent round tubes refers to the distance between the centers of the two adjacent round tubes. The length of the round tube can be 0.1-2 m. The length of the round tube refers to the distance along the direction of fiber ejection.
[0042] According to the present invention, preferably, the core layer material melt is obtained by melting the core layer material at 220-280°C.
[0043] According to the present invention, preferably, the skin layer material melt is obtained by melting the skin layer material at 200-280°C.
[0044] In the present invention, it is understood that the temperature of the core layer material melt and the skin layer material melt refers to the temperature of the spinneret when the core layer material melt and the skin layer material melt are extruded from the spinneret outlet.
[0045] The second aspect of the present invention provides a composite polyester fiber prepared by the method described above.
[0046] According to the present invention, preferably, the average diameter D of the composite polyester fiber is 18-30 μm, and the standard deviation of the diameter is ≤2.2 μm.
[0047] In the present invention, the average diameter of the composite polyester fiber can be 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, and a range formed by any two of the above points. The standard deviation of the diameter of the composite polyester fiber can be 2.2 μm, 2 μm, 1.8 μm, 1.6 μm, 1.4 μm, 1.2 μm, 1 μm, 0.8 μm, 0.6 μm, 0.4 μm, 0.2 μm, 0.1 μm, and a range formed by any two of the above points, for example, 0.1-2.2 μm.
[0048] In the present invention, the test method of the diameter standard deviation is: randomly select 50 composite polyester fibers, randomly cut a small section from each, take a scanning electron microscope (SEM) photo, and measure the diameter of each fiber from the photo, accurate to 0.1 μm, and then calculate the standard deviation of these diameter values according to the standard deviation calculation method.
[0049] In the present invention, the composite polyester fiber refers to a composite polyester fiber having a length greater than 150 mm.
[0050] According to the present invention, the inventors have further discovered that when a fiber cloth prepared from polyester fibers whose mass ratio x of the core layer material to the skin layer material and the average diameter D of the polyester fibers satisfy the relationship of the following formula (1) is used for cell culture, it can improve the sugar metabolism capacity of cells.
[0051]
[0052] More preferably, when the mass ratio of the core layer material to the skin layer material of the composite polyester fiber is 2-3 and satisfies the formula (1), the sugar metabolism capacity of cells can be further improved when the composite polyester fiber is used for cell culture.
[0053] A third aspect of the present invention provides a polyester fiber cloth, which is prepared by using the polyester fiber mentioned above.
[0054] According to the present invention, preferably, the thickness of the polyester fiber cloth is 0.4-0.5 mm and the surface density is 80-130 g / m 2 .
[0055] The fourth aspect of the present invention provides use of the polyester fiber or the polyester fiber cloth described above in cell culture.
[0056] According to the present invention, preferably, the application includes increasing the sugar metabolism rate of cells. Preferably, using the fiber cloth of the present invention for cell culture can increase the sugar metabolism rate of cells to above 15 g / day, for example, 15-30 g / day.
[0057] The present invention will be described in detail below by way of examples. In the following examples,
[0058] Unless otherwise specified, the spinneret is manufactured by Changzhou Jier Precision Machinery Manufacturing Co., Ltd. and is customized as required.
[0059] The Sb content in the core layer material and the skin layer material is less than 20 ppm.
[0060] The room temperature is about "15-20℃".
[0061] In the following embodiments, the homemade polyester involved is prepared by mixing PTA (terephthalic acid, analytical grade), EG (ethylene glycol, analytical grade) and an optional comonomer Y (e.g., cyclohexanedimethanol, analytical grade) in a reactor according to the required amount of the product, heating to 258-263° C., reacting for about 1 hour, then adding tetrabutyl titanate, raising the temperature to 275-290° C., and evacuating with an oil pump, reacting for about 2 hours to obtain the desired PET.
[0062] Example 1
[0063] Homopolyethylene terephthalate (manufacturer: Sinopec Yizheng Chemical Fiber Co., Ltd., hereinafter referred to as "Yizheng Chemical Fiber", model FG600, intrinsic viscosity 0.675 dL / g, standard deviation of intrinsic viscosity 0.003 dL / g, melting point 261°C) was used as the core material. Copolyethylene terephthalate (Yizheng Chemical Fiber, model FG702, intrinsic viscosity 0.78 dL / g, standard deviation of intrinsic viscosity 0.006 dL / g, comonomer cyclohexanedimethanol, comonomer content 15 mol%, melting point 140°C) was used as the skin material. The mass ratio of the core material to the skin material was 3, and the core material was extruded from a spinneret at an outlet temperature of about 280°C. There are 48 small holes with skin-core concentric structure distributed on the spinneret, the inner diameter of the inner hole is 20 microns, the range (the diameter of the largest hole minus the diameter of the smallest hole) is 1.2 microns, and the inner diameter of the outer hole is 30 microns, the range is 1.1 microns. After the polymer melt is extruded from the spinneret, it is blown and cooled with room temperature wind of 1.5-1.8m / s, and the cooled fibers are evenly or nearly evenly fed into 5 steel round tubes (the inner diameter of the round tube is 2cm, the distance between two adjacent round tubes is 3.5cm, and the length of the round tube is 1m), and the cooled filaments are stretched in the round tube at a wind speed of about 4000-4500m / min to obtain composite polyester fibers.
[0064] Example 2
[0065] The method of Example 1 was followed, except that copolyethylene terephthalate (Yizheng Chemical Fiber, model BG804, intrinsic viscosity 0.801 dL / g, standard deviation of intrinsic viscosity 0.005 dL / g, comonomer cyclohexanedimethanol, comonomer content 0.75 mol%, melting point 237°C) was used as the skin material.
[0066] Example 3
[0067] The method of Example 1 is followed, except that the mass ratio of the core layer material to the skin layer material is 2, the inner diameter of the inner hole of the spinneret used is 18 microns, the range is 1.1 microns, and the inner diameter of the outer hole is 32 microns, the range is 1.6 microns.
[0068] Example 4
[0069] The method of Example 1 is followed, except that the mass ratio of the core layer material to the skin layer material is 3.6.
[0070] Example 5
[0071] The method of Example 1 is followed, except that the mass ratio of the core layer material to the skin layer material is 1.6.
[0072] Comparative Example 1
[0073] The method of Example 1 is followed, except that the mass ratio of the core layer material to the skin layer material is 1.
[0074] Comparative Example 2
[0075] The method of Example 1 is followed, except that the mass ratio of the core layer material to the skin layer material is 5.
[0076] Comparative Example 3
[0077] The method of Example 1 was followed, except that the raw material used for homopolyethylene terephthalate was homemade polyester, the intrinsic viscosity was 0.51 dL / g, the standard deviation of the intrinsic viscosity was 0.01 dL / g, and the melting point was 260°C.
[0078] Comparative Example 4
[0079] The method of Example 1 was followed, except that the holes of the spinneret were not concentric circles, but parallel structures that divided the circle into two. The inner diameter of the circular spinneret holes was 30 μm, and the range was 1.1 μm.
[0080] Comparative Example 5
[0081] The method of Example 1 is followed, except that the spinneret has a larger aperture range, with the inner diameter of the inner layer hole being 20 μm and the range being 3.6 μm, and the inner diameter of the outer layer hole being 30 μm and the range being 5.3 μm.
[0082] Comparative Example 6
[0083] The method of Example 1 was followed, except that the raw material model of the homopolyethylene terephthalate used was BG85 from Yizheng Chemical Fiber, with an intrinsic viscosity of 0.879 dL / g, a standard deviation of the intrinsic viscosity of 0.005 dL / g, and a melting point of 248°C.
[0084] Comparative Example 7
[0085] The method of Example 1 is followed, except that the raw material used for homopolyethylene terephthalate is homemade polyester, with an intrinsic viscosity of 0.675 dL / g, a standard deviation of the intrinsic viscosity of 0.031 dL / g, and a melting point of 260°C; the raw material used for copolyethylene terephthalate is homemade polyester, with an intrinsic viscosity of 0.782 dL / g, a standard deviation of the intrinsic viscosity of 0.025 dL / g, and a melting point of 143°C, and the comonomer is cyclohexanedimethanol, with a comonomer content of 15 mol%.
[0086] Comparative Example 8
[0087] The method of Example 1 was followed, except that the raw material model of the homopolyethylene terephthalate used was BG804 from Yizheng Chemical Fiber, the intrinsic viscosity was 0.801 dL / g, the standard deviation of the intrinsic viscosity was 0.005 dL / g, and the melting point was 237°C.
[0088] Comparative Example 9
[0089] The method of Example 1 was followed, except that the raw material model of the co-polyethylene terephthalate was BG85 from Yizheng Chemical Fiber, the intrinsic viscosity was 0.879 dL / g, the standard deviation of the intrinsic viscosity was 0.005 dL / g, and the melting point was 248°C.
[0090] Test Example 1
[0091] (1) The average diameter of the composite polyester fiber was measured and the standard deviation of the diameter was calculated. The test results are shown in Table 1.
[0092] The test method for the average diameter of the composite polyester fiber is as follows: randomly select 50 composite polyester fibers, randomly cut a small section, take a scanning electron microscope (SEM) photo, and measure the diameter of each fiber from the photo, accurate to 0.1μm, and then calculate the average value of these diameter values according to the average value calculation method; and calculate the standard deviation of these diameter values according to the standard deviation calculation method. The test results are shown in Table 1.
[0093] Test Example 2
[0094] The composite polyester fibers obtained in the above-mentioned embodiments and comparative examples were laid out using a web laying machine, and then the fiber cloth web of a certain thickness was hot pressed at 190-200°C using a non-embossed polished hot roller to obtain a fiber cloth of a specific thickness. The surface density of the fiber cloth is tested by using a 1 / 10,000 balance to measure the surface density of 1 cm 2 The fiber cloth of the area is weighed, and then the mass of the fiber cloth is divided by its area; the test method of the fiber cloth thickness is: using a dial thickness gauge (model 547-313) from Suzhou Quantum Instrument Co., Ltd. The surface density and thickness of the fiber cloth are measured as shown in Table 1.
[0095] Pretreatment and sterilization of fiber cloth: Soak the fiber cloth in a 7 wt% hydrogen peroxide aqueous solution at room temperature for 60 minutes; then use ultrapure water to ultrasonically clean the fiber cloth, and then dry it at 80°C. After drying, sterilize the fiber cloth with high-temperature steam at a temperature of 121°C for 60 minutes.
[0096] Then the sugar metabolism ability of Vero cells was tested when the sterilized fiber cloth was used as a carrier. The test method for sugar metabolism is: cut the fiber cloth into small pieces of 6mm×6mm fiber cloth, place 100g of 6mm×6mm fiber cloth, 8L PBS buffer and about 200mL of 199 culture medium (purchased from Beijing Tsinghua Tianyi Biotechnology Co., Ltd.) in a 10L basket reactor, add 10% high-quality newborn calf serum (purchased from Lanzhou Minhai Biotechnology Co., Ltd.) relative to the culture medium, and add an appropriate amount of 20% by weight concentration of glucose so that the total glucose concentration is 0.5% by weight. Inoculate Vero cells (purchased from the National Biomedical Experimental Cell Resource Bank, 4th generation Vero cells, every 1cm 2 The inoculation amount of cells on the fiber cloth was 0.5×10 6 ), aeration culture at 37°C, pH 7.3, DO (percentage of dissolved oxygen in saturated dissolved oxygen) 60%, 5% carbon dioxide concentration, and slow stirring during culture for 7 days. Samples were taken every 24 hours and the glucose content was detected using a glucose detection kit (purchased from Nanjing Jiancheng Bioengineering Institute), and the glucose concentration was supplemented to 0.5% by weight with a 20% by weight glucose solution. The measured reduction in glucose content was converted into a glucose consumption rate value in g / day, and a curve of glucose consumption rate versus culture time was drawn, and then the value at 100h was taken as the 100h sugar metabolism rate value. The 100h sugar metabolism rate value is shown in Table 1.
[0097] Table 1
[0098]
[0099] From the results in Table 1, it can be seen that the diameter standard deviation of the composite polyester fiber prepared by the method of the present invention is small, so the composite polyester fiber prepared by the method of the present invention has better uniformity. Preferably, the composite polyester fiber of the present invention can significantly improve the sugar metabolism ability of cells.
[0100] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a composite polyester fiber, characterized in that: The method comprises: melting the core layer material and the skin layer material respectively to obtain a melt, and then spinning the melt to obtain a composite polyester fiber with a skin-core structure; The melting point of the core material is higher than that of the skin material by more than 22°C; the intrinsic viscosity of the skin material is 0.01-0.15 dL / g higher than that of the core material, and the standard deviation of the intrinsic viscosities of the core material and the skin material is ≤0.02 dL / g; the mass ratio of the core material to the skin material is x, 1.5≤x≤4; The spinneret holes of the spinneret plate used in the spinning process are in the shape of concentric circles, the difference between the maximum diameter and the minimum diameter of each circle of the spinneret holes is ≤2 μm, and the difference between the maximum diameter and the minimum diameter of each outer circle is ≤2 μm.
2. The method according to claim 1, wherein: The core layer material is homopolyethylene terephthalate; Preferably, the intrinsic viscosity of the homopolyethylene terephthalate is 0.6-0.8 dL / g, more preferably 0.65-0.7 dL / g, and the melting point is above 240°C, more preferably 245-280°C.
3. The method according to claim 2, wherein: The standard deviation of the intrinsic viscosity of the homopolyethylene terephthalate is ≤0.01 dL / g, preferably ≤0.005 dL / g.
4. The method according to claim 1, wherein: The skin material is copolyethylene terephthalate; Preferably, the intrinsic viscosity of the copolyethylene terephthalate is 0.5-0.9 dL / g, more preferably 0.6-0.8 dL / g, and the melting point is below 240°C, more preferably 130-240°C.
5. The method according to claim 4, wherein: The standard deviation of the intrinsic viscosity of the copolyethylene terephthalate is ≤0.015 dL / g, preferably ≤0.01 dL / g.
6. The method according to claim 4, wherein: The copolyethylene terephthalate comprises structural units derived from terephthalic acid, ethylene glycol and comonomer Y, and the content of the structural units derived from comonomer Y in the copolyethylene terephthalate is 0.6-18 mol %, more preferably 0.7-15 mol %; Preferably, the comonomer Y is selected from at least one of dicarboxylic acids, diols and tetraols.
7. The method according to claim 1, wherein: The inner diameter of the inner hole on the spinneret is 15-25 μm, and the inner diameter of the outer ring is 25-35 μm.
8. The composite polyester fiber prepared by the method according to any one of claims 1 to 7; Preferably, the average diameter D of the composite polyester fiber is 18-30 μm, and the standard deviation of the diameter is ≤2.2 μm.
9. A polyester fiber cloth, characterized in that: The polyester fiber cloth is prepared by using the composite polyester fiber described in claim 8.
10. Use of the composite polyester fiber according to claim 8 or the polyester fiber cloth according to claim 9 in cell culture.
Citation Information
Patent Citations
A method for preparing highly uniform military-grade soft polyester industrial yarn
CN107893264B
Production apparatus and preparation method for high-uniformity superfine polyester fibers
WO2022134653A1
Method for preparing sheath core composite long fiber with low melting point
CN101619506A
Method for preparing continuous polymerization directly-spun high-shrinkage polyester staple fibers
CN101787584A
Filaments for beverage extraction filter and woven fabric comprising same for beverage extraction filter
CN110446668A